2012
DOI: 10.1017/s0008423912000352
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity Conundrum: Why Hasn't the Gender Gap in Subjective Political Competence Closed?

Abstract: Abstract.In the 1960s, the gender gap in subjective political competence was assumed to reflect women's lack of socioeconomic resources, their confinement to the domestic sphere and their gender role socialization. Since then, women have moved into the labour force in vast numbers and conceptions of gender roles have been radically altered under the influence of the feminist movement. Yet, the gender gap in subjective political competence persists. This paper uses the Canadian Election Studies (1965–2008) to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
(27 reference statements)
1
15
0
2
Order By: Relevance
“…The study's findings suggest female clinical social workers' perspectives of political participation and their own potential for political involvement align with the extant literature on women's political participation (e.g., Barabas, Jerit, Pollock, & Rainey, 2014;Dolan, 2010;Fox, 2011;Hannagan, Littvay, & Popa 2014;Thomas, 2012). The participants described their own expectations and their families' expectations that they would focus on family caretaking to the exclusion of political involvement.…”
Section: Discussionsupporting
confidence: 73%
“…The study's findings suggest female clinical social workers' perspectives of political participation and their own potential for political involvement align with the extant literature on women's political participation (e.g., Barabas, Jerit, Pollock, & Rainey, 2014;Dolan, 2010;Fox, 2011;Hannagan, Littvay, & Popa 2014;Thomas, 2012). The participants described their own expectations and their families' expectations that they would focus on family caretaking to the exclusion of political involvement.…”
Section: Discussionsupporting
confidence: 73%
“…With the exception of voting, men engage in these activities more than women (Burns, Schlozman, & Verba, ). Men also display greater political engagement in that they have comparatively greater political knowledge (Delli Carpini & Keeter, ; Mondak & Anderson, ), political interest, and confidence in their political competence (Burns et al, ; Thomas, ). These broad engagement factors strongly predict political participation, since not wanting to participate is one reason why many disengage from politics (Verba et al, ).…”
Section: Gender In the Citizenrymentioning
confidence: 99%
“…American National Election Studies (ANES) data collected since 1947 demonstrated a rather stable knowledge gap such that women’s accuracy on a five‐question political knowledge battery is 20–35% lower than that of male respondents (Delli Carpini & Keeter, ; McGlone, Aronson, & Kobrynowicz, ). Larger gaps—15 points and 12 points, respectively—separate men and women with regard to paying attention to national politics (Verba, Burns, & Scholzman, ) and subjective political competence (Thomas, ). Finally, modest gaps of about 4 points occur on voter turnout, the one area where women participate more than men.…”
Section: Gender In the Citizenrymentioning
confidence: 99%
“…A typical explanation for women's lower rates of participation in party and electoral politics is resource disparity. This includes both socioeconomic resources such as time and money (Norris and Lovenduski, 1995) and political resources such as knowledge (Pruysers and Blais, 2014), interest (Delli Carpini and Keeter, 1996) and efficacy (Burns et al, 2001; Thomas, 2012). Given that women tend to have fewer of these resources, it should not be surprising that party members are significantly more likely to be men or that women candidates tend to have a shorter history with their party and attract significantly fewer volunteers 3 .…”
Section: Theory and Hypothesesmentioning
confidence: 99%